MODEL STRATEGI PEMBANGUNAN LESTARI UNTUK TASIK CHINI, PAHANG (A MODEL FOR STRATEGIC SUSTAINABLE DEVELOPMENT FOR TASIK CHINI, PAHANG) - Asmawi, M. Zainora (2018)
This works addresses a model of strategic sustainable development for Tasik Chini, Pahang in relation to conserving the natural resources. The existence of various ecosystems such as lakes, forestry and hilly areas are essential to accommodate the necessity of Orang Asli and villagers of nearby areas. This disclosure contains list of environmental sensitive areas, including of types and level (information in table and plan forms). The mapping of spatial data is reflected the true picture of level of environmental quality for Tasik Chini, Pahang.